2005
DOI: 10.1158/1078-0432.ccr-05-1426
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Interleukin-9 in Nasal Natural Killer/T-Cell Lymphoma Cell Lines and Patients

Abstract: Purpose: Nasal natural killer (NK)/T-cell lymphoma is associated with EBV and has distinct clinical and histologic features. However, little is known about its genetic features. In this study, we examined the genes expressed by SNK-6 and SNT-8 cells, which were established from nasal NK/T-cell lymphomas, and found that interleukin (IL)-9 was specifically expressed in these two cell lines. Experimental Design: cDNA array was used to examine the genes expressed by SNK-6 and SNT-8 cells. Expression of IL-9 and IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 41 publications
1
67
0
Order By: Relevance
“…Only a few genome-wide profiling studies using NK-cell lines 13,14 and a limited number of NK-cell 15 and gd T-cell lymphoma cases have been performed. 16 In this study, we have defined molecular signatures for ENKTL and related malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few genome-wide profiling studies using NK-cell lines 13,14 and a limited number of NK-cell 15 and gd T-cell lymphoma cases have been performed. 16 In this study, we have defined molecular signatures for ENKTL and related malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that SNK6 cells produce several cytokines and chemokines such as interferon (IFN)-γ, interleukin (IL)-9, IL-10 and interferon-γ-inducible protein (IP)-10, which play roles in cellular proliferation and invasion in an autocrine manner [7][8][9]. Furthermore, monocytes attracted by IP-10 enhance the proliferation via cell-to-cell contact [10].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with our previous findings (Lin et al, 2014), we confirmed that IL-17 deficiency promoted MPE formation by enhancing the angiogenesis and proliferation of pleural tumors, and that in vivo administration of anti-IL-17 mAb in WT mice was able to promote MPE formation by increasing tumor angiogenesis and proliferation, while in vivo administration of rmIL-17 in IL-17 / mice was able to inhibit MPE formation by diminishing tumor angiogenesis and proliferation. Previous studies have suggested that IL-9 plays an important role in NK/T-cell lymphoma possibly via an autocrine mechanism (Nagato et al, 2005). Purwar and colleagues (Purwar et al, 2012) have demonstrated that that mice deficient in Th17 cell development have substantial resistance to melanoma growth in a IL-9-dependent manner; and treatment with exogenous IL-9 inhibits tumor growth in vivo.…”
Section: Discussionmentioning
confidence: 99%